Proceedings of the 2015 Annual Conference on Genetic and Evolutionary Computation 2015
DOI: 10.1145/2739480.2754721
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Objectives Relationships in Multiobjective Problems Using Trade-Off Region Maps

Abstract: Understanding the relationships between objectives in manyobjective optimisation problems is desirable in order to develop more effective algorithms. We propose a technique for the analysis and visualisation of complex relationships between many (three or more) objectives. This technique looks at conflicting, harmonious and independent objectives relationships from different perspectives. To do that, it uses correlation, trade-off regions maps and scatter-plots in a four step approach. We apply the proposed te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…This paper has shown that the proposed technique is an effective and efficient approach to tackle real-world multiobjective highly-constrained combinatorial optimisation problems, by combining the effectiveness (but often computationally expensive) of state-of-the-art multiobjective algorithms with the efficiency of well-targeted single-objective optimisation through goal programming. For this, the multiobjective analysis technique proposed by (Pinheiro et al, 2015(Pinheiro et al, , 2017 offers an effective tool to analyse the relationships between objectives in multiobjective optimisation problems and determine the degree of similarity in the fitness landscape of different problem instances.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper has shown that the proposed technique is an effective and efficient approach to tackle real-world multiobjective highly-constrained combinatorial optimisation problems, by combining the effectiveness (but often computationally expensive) of state-of-the-art multiobjective algorithms with the efficiency of well-targeted single-objective optimisation through goal programming. For this, the multiobjective analysis technique proposed by (Pinheiro et al, 2015(Pinheiro et al, , 2017 offers an effective tool to analyse the relationships between objectives in multiobjective optimisation problems and determine the degree of similarity in the fitness landscape of different problem instances.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work proposed a technique to analyse and visualise complex objective relationships and fitness landscapes in multiobjective problems (Pinheiro et al, 2015(Pinheiro et al, , 2017. Later, Pinheiro et al (2018) introduced a methodology to exploit the recurring similarity between instances of a multiobjective workforce scheduling and routing optimisation problem, in order to solve instances of the same problem scenario more efficiently.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the technique proposed i this paper can be of practical use in that type of problems. In addition, the multiobjective analysis technique proposed by (Pinheiro et al, 2015(Pinheiro et al, , 2017 offers an effective tool to evaluate whether using goal programming to solve the problem is applicable or not.…”
Section: Resultsmentioning
confidence: 99%
“…As preliminary work, we applied the analysis technique proposed by Pinheiro et al (2015Pinheiro et al ( , 2017 on all instances considered here. The technique consists of performing four steps: first the global pairwise relationships are analysed using the Kendall correlation method; then the ranges of the values found on the given approximation front are estimated and assessed; next these ranges are used to plot a map using Gray code, similar to Karnaugh maps, that has the ability to highlight the trade-offs between multiple objectives; and finally local relationships are identified using scatter plots.…”
Section: The Workforce Scheduling and Routing Problemmentioning
confidence: 99%
See 1 more Smart Citation